Assessment of XAF1 as A Biomarker to Differentiate Hepatocellular Carcinoma from Nonneoplastic Liver Tissues - Lin, Ying; Li, Wei (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: XIAP-associated factor 1 (XAF1) expression has been shown to be related with apoptosis in hepatocellular carcinoma (HCC). However, the correlation of XAF1 expression with HCC tumor grade has not been intensively assessed. XIAP-associated factor-1 (XAF1) is an important apoptosis inducer in human HCC. The aim of this study is to determine the correlation between XAF1 expression and HCC histopathological grades. Methods: The mRNA levels of XAF1 in 24 paired HCC-nonneoplastic specimens were quantified by real-time reverse transcription PCR (RT-PCR). Protein levels of XAF1 in 110 paired HCC-noncancer tissues were investigated by immunostaining specimens on a tissue microarray (TMA). Correlations between XAF1 mRNA levels or protein expression and clinicopathological features were assessed by statistical analysis. Results: Both XAF1 mRNA and protein were significantly under-expressed in HCC tissues compared to their nonneoplastic counterparts. No significant relationship was found between XAF1 mRNA or protein expression and histological tumor grade. Conclusion: All these data suggest that XAF1 is a potential biomarker for differentiating HCC with noncancerous tissues.